Real time implementation of STATCOM to analyze transient and dynamic characteristics of wind farm - Sattar, A.; Al-Durra, A.; Muyeen, S.M. (2011)
In this paper, a grid connected wind farm with a static synchronous compensator (STATCOM) is modeled in Real Time Digital Simulator (RTDS) environment to analyze its dynamic and transient characteristics in real system. This work is also a part of future power hardware-in-loop (PHIL) test and therefore, individual components are models considering practical viewpoints. Wind turbines and generators of a wind farm, power grid, and control system are realized in the large time-step main network. However, 2-level voltage source converter based STATCOM is modeled in RTDS small time-step environment to adapt with higher switching frequency, where interface transformer is used to link the different time step sub-networks. Suitable control strategy for STATCOM is developed to augment the stability of wind farm considering that capacitor connected at the terminal of wind generator is reduced up to certain percentage. Option for integrating anemometer for dynamic characteristics analysis, difficulties of STATCOM switching schemes for implementing PHIL testing in RTDS environment are discussed. Results are compared with Laboratory standard power system software PSCAD/EMTDC and the advantages of using RTDS in dynamic and transient characteristics analyses of wind farm are also demonstrated clearly.